1992
DOI: 10.1128/jvi.66.1.172-182.1992
|View full text |Cite
|
Sign up to set email alerts
|

Native but not denatured recombinant human immunodeficiency virus type 1 gp120 generates broad-spectrum neutralizing antibodies in baboons

Abstract: The protection of individuals from human immunodeficiency virus type 1 (HIV-1) infection with an envelope subunit derived from a single isolate will require the presentation of conserved epitopes in gp120. The objective of the studies presented here was to test whether a native recombinant gp120 (rgp120) immunogen would elicit responses to conserved neutralization epitopes that are not present in a denatured recombinant gp120 antigen from the same virus isolate. In a large study of 51 baboons, we have generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(39 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…These results are in agreement with those obtained by other authors who investigated the immunogenicity of different HIVderived peptidic constructs in monkey models, including baboons, macaque, and chimpanzees [16,[18][19][20]. In most of these studies several injections of the immunogen were required in order to achieve antibody titres able to neutralize HIV-1 in vitro [19]. On the other hand, in squirrel monkeys, high titre of serum antibodies above 10 ÿ 6 and neutralizing antibody titres just below 10 ÿ 2 could be reached after two immunizations in some animals.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in agreement with those obtained by other authors who investigated the immunogenicity of different HIVderived peptidic constructs in monkey models, including baboons, macaque, and chimpanzees [16,[18][19][20]. In most of these studies several injections of the immunogen were required in order to achieve antibody titres able to neutralize HIV-1 in vitro [19]. On the other hand, in squirrel monkeys, high titre of serum antibodies above 10 ÿ 6 and neutralizing antibody titres just below 10 ÿ 2 could be reached after two immunizations in some animals.…”
Section: Discussionsupporting
confidence: 92%
“…Using recombinant gp160 protein in different adjuvant formulations, we showed that high titres of specific antibodies could be induced after only two immunizing doses of the protein, and that these antibodies recognized the protein in Western blot experiments and neutralized the activity of the virus in vitro. These results are in agreement with those obtained by other authors who investigated the immunogenicity of different HIVderived peptidic constructs in monkey models, including baboons, macaque, and chimpanzees [16,[18][19][20]. In most of these studies several injections of the immunogen were required in order to achieve antibody titres able to neutralize HIV-1 in vitro [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The existence of both monoclonal and polyclonal serum anti-gpl20 antibodies against conserved epitopes such as the CD4 binding site with broad neutralizing reactivity has been already demonstrated by one of us [32] and others [36,37). Vaccine work in baboons further demonstrates that with an appropriate immunogen and regimen it is possible to broaden the immune response to divergent isolates [38]. Similarly, therapeutic approaches should avoid reinforcing established restricted clonal responses of B-cells producing ineffective antibodies and be able to restore a polyclonal immune response.…”
Section: Discussionmentioning
confidence: 89%
“…To investigate the utility of a more direct method of assessing vaccine response, we developed a sandwich ELISA method to separately measure antibodies against native glycoproteins, which are potentially protective, and antibodies against denatured glycoproteins or internal viral proteins ('unfoldons'), 12 which are not protective. [13][14][15][16][17][18] Direct coating of virus onto microtiter plate wells results in virus disruption and denaturing some proportion of surface glycoproteins. Thus, direct virus coating will capture all anti-influenza antibodies against native, denatured, and internal proteins.…”
Section: Introductionmentioning
confidence: 99%